2011
DOI: 10.1590/s1516-35982011000900024
|View full text |Cite
|
Sign up to set email alerts
|

Levels of multiple supplements or nitrogen salt for beef heifers in pasture during the dry season

Abstract: -The study assessed performance, microbial protein synthesis, intake and digestibility of nutrients by beef heifers receiving levels of multiple supplements or nitrogen salt, in a self-controlled intake, on pasture, during the dry season. Thirty-five beef heifers, from 6 to 9 months of age and average initial body weight of 203.4 + 4.5 kg, were used. Study factors were: control -mineral mixture; nitrogen salt -50% of urea + mineral mixture, at proportion of 1:1, and 50% of corn (75% of crude protein); levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
1
15
1
5
Order By: Relevance
“…Overall, there were no differences in performance for animals that received self-feed supplement and those which received concentrate supplementation with low urea levels (VALENTE et al, 2011). According to Bohnert et al (2002a), the ability of ruminants supplemented at a lower frequency to maintain performance levels is probably a result of the same digestibility of retained N when compared with daily supplementation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Overall, there were no differences in performance for animals that received self-feed supplement and those which received concentrate supplementation with low urea levels (VALENTE et al, 2011). According to Bohnert et al (2002a), the ability of ruminants supplemented at a lower frequency to maintain performance levels is probably a result of the same digestibility of retained N when compared with daily supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…Self-feed supplementation also has a positive effect on nutritional traits (ZERVOUDAKIS et al, 2008), with positive responses in performance from grazing beef cattle (VALENTE et al, 2011). Zervoudakis et al (2010) observed that self-feed supplements do not influence nutrient intake, ruminal passage rate, or total retention time in the gastrointestinal tract of steers on tropical pasture.…”
Section: Discussionmentioning
confidence: 99%
“…A massa de MSpd expressa em função do peso corporal (PC), remete a idéia quantitativa e qualitativa da forragem disponível momentaneamente ao animal, independente da taxa de lotação (VALENTE et al, 2011a).…”
Section: Discussionunclassified
“…Nas amostras de forragem obtidas via simulação manual do pastejo e dos concentrados foram quantificados os teores de matéria seca (MS); matéria mineral (MM); proteína bruta (PB), extrato etéreo (EE) e lignina, (SILVA; QUEIROZ, 2002); fibra em detergente neutro (FDNcp), (MERTENS, 2002), utilizando-se α-amilase termoestável e omitindo-se o uso de sulfito de sódio, foram realizadas correções para proteína e cinzas na FDN, quantificou-se o teor de nitrogênio insolúvel em detergente neutro (NIDN) e o teor de fibra em detergente ácido (FDA) (VAN SOEST; ROBERTSON, 1985), com correções para proteína e cinzas; fibra em detergente neutro indigestível (FDNi), (VALENTE et al, 2011b), obtida após a incubação em sacos (F57 Ankom®) in situ por 288 horas. Nas amostras de forragem destinadas ao cálculo da massa de MS e MSpd foram quantificados os teores de MS; FDNcp e FDNi, conforme descrito anteriormente.…”
Section: Methodsunclassified
“…Nas amostras de forragem obtidas via simulação manual do pastejo e dos concentrados foram quantificados os teores de matéria seca (MS); matéria mineral (MM); proteína bruta (PB), extrato etéreo (EE), segundo Silva e Queiroz (2002); fibra em detergente neutro (FDNcp), segundo Mertens (2002), utilizando-se α-amilase termoestável e omitindo-se o uso de sulfito de sódio, foram realizadas correções para proteína e cinzas na FDN, quantificou-se o teor de nitrogênio insolúvel em detergente neutro (NIDN) seguindo as recomendações de Van Soest e Robertson (1985), com correções para cinzas; fibra em detergente neutro indigestível (FDNi), de acordo com Valente et al (2011b), obtida após a incubação em sacos (F57 Ankom ® ) in situ por 288 horas. Nas amostras de forragem destinadas ao cálculo da massa de MS e MSpd foram quantificados os teores de MS; FDNcp e FDNi, conforme descrito anteriormente.…”
Section: Análises Químicasunclassified